Impaired immunomodulatory capacity in adipose tissue‐derived mesenchymal stem/stromal cells isolated from obese patients. Issue 18 (21st August 2021) - Zhu, Xiang‐Yang; Klomjit, Nattawat; Conley, Sabena M.; Ostlie, Megan M.; Jordan, Kyra L.; Lerman, Amir; Lerman, Lilach O.
Abstract: Immune‐modulatory properties of adipose tissue‐derived mesenchymal stem/stromal cells (MSCs) might be susceptible to metabolic disturbances. We hypothesized that the immune‐modulatory function of MSCs might be blunted in obese human subjects. MSCs were collected from abdominal subcutaneous fat of obese and lean subjects during bariatric or kidney donation surgeries, respectively. MSCs were co‐cultured in vitro for 24 h with M1 macrophages, which were determined as M1or M2 phenotypes by flow cytometry, and cytokines measured in conditioned media. In vivo, lean or obese MSCs (5 × 10 5 ), or PBS, were injected into mice two weeks after unilateral renal artery stenosis (RAS) or sham surgeries ( n = 6 each). Fourteen days later, kidneys were harvested and stained with M1 or M2 markers. Lean MSCs decreased macrophages M1 marker intensity, which remained elevated in macrophages co‐cultured with obese MSCs. TNF‐α levels were four‐fold higher in conditioned media collected from obese than from lean MSCs. RAS mouse kidneys were shrunk and showed increased M1 macrophage numbers and inflammatory cytokine expression compared with normal kidneys. Lean MSCs decreased M1 macrophages, M1/M2 ratio and inflammation in RAS kidneys, whereas obese MSCs did not. MSCs isolated from lean human subjects decrease inflammatory M1 macrophages both in vivo and in vitro, an immune‐modulatory function which is blunted in MSCs isolated from obese subjects.